O tratamento dado à variação linguística do tempo futuro do presente em livros didáticos de língua portuguesa dos anos finais do ensino fundamental - Costa, Izabelle de Vasconcelos (2023)
This research aims to describe the treatment given to the expression of the linguistic variation of the future tense of the present in Portuguese language textbooks, specifically in the Se Liga na Língua collection: Reading, Text Production and Language (Ormundo; Sinicalchi, 2018), intended for the stage of the final years of Elementary School, 6th, 7th, 8th and 9th grade, approved by the 2020 National Book and Didactic Material Program (PNLD). For this purpose, we present reflections about the studies of the language inserted in the theoretical-methodological assumptions of variationist Sociolinguistics (Labov, 2008 [1972]) which, in general, in linguistic research, prioritize the relationship between language and society and the assumptions of educational Sociolinguistics (Bagno, 2007; Bortoni-Ricardo, 2014; Faraco, 2008; Zilles; Faraco, 2015) that deal with the implications of the sociolinguistic perspective for teaching. With the publication of the National Common Curricular Base - BNCC, a normative document that foresees the teaching of linguistic variation in the Portuguese language component, the interest arose in researching the approach of linguistic phenomena in textbooks, specifically the approach of the object of this research, which is the Linguistic variation of the future tense of the present. It is interesting to point out that our research has a qualitative approach, being characterized as exploratory. The method used is hypothetical-deductive, with documentary data collection. The analysis of linguistic phenomena in the collections was carried out considering three categories: i. Theoretical orientation in relation to the conception of language adopted in the teacher's manuals; ii. Theoretical guidance regarding the treatment given to linguistic variation, adopted in teacher manuals; and iii. Pedagogical guidance present in the proposed activities in the student's book involving the phenomenon under analysis. The results showed that the alternation between the variants of verb tenses that express the future of the present appears tangentially in Portuguese language textbooks, with pedagogical proposals making almost exclusive use of the standard norm, considering that this is the main reference for the teaching of the Portuguese language.